10.1111/acn.v9999.9999 (CrossRef Listing of Deleted DOIs, 2000)
Background The value of additional lesion sets beyond pulmonary vein isolation (PVI) for atrial fibrillation (AF) ablation is unclear. However, existing studies evaluated the utility of substrate modification with conventional energy sources. There is limited data evaluating PVI with posterior wall isolation (PWI) using pulsed field ablation (PFA). Methods We studied consecutive cases of patients with paroxysmal AF undergoing first-time ablation with PFA between May 6, 2024 and March 10, 2025. Procedural data collected included the number of PFA applications administered, total procedure time, and major periprocedural complications. Clinical data collected included atrial tachyarrhythmia (ATA) recurrence, stroke, and major bleeding at 1-year follow-up. Outcomes were compared in patients undergoing PVI alone versus PVI plus PWI. Results A total of 249 patients were included in this study (104 PVI alone, 145 PVI plus PWI). There was no difference in ATA recurrence by Kaplan-Meier survival analysis comparing PVI alone versus PVI plus PWI (log rank test p = 0.89). When comparing PVI alone versus PVI plus PWI, there was no difference in ATA recurrence at 1 year (16% vs. 16%; p = 0.92), AF burden on continuous monitoring (2% vs. 2%; p = 0.81), total procedure time (114 vs. 107 min; p = 0.14), or major periprocedural complications (0 vs. 3; p = 0.14). Conclusion PFA for paroxysmal AF with PVI alone or PVI plus PWI produces similar sinus rhythm maintenance without affecting procedure times or complication rates.